Adesão à intervenção nutricional baseada na dieta do mediterrâneo em pacientes após síndrome coronariana aguda - Lins, Suelen Dalbosco (2017)
Introduction: Scientific evidences demonstrate that Mediterranean Diet is a protective factor for several kinds of chronic non-communicable diseases, such as cardiovascular diseases. This dietary pattern is essential as preventive and treatment measure for these diseases. The accession to changes in habit is a dynamic process, challenging for both patients and healthcare professionals. Nevertheless, in Brazil there are few works that show adherence to diet in patients with Acute Coronary Syndrome. Objective: To assess the accession to a nutritional intervention based on Mediterranean Diet in patients after Acute Coronary Syndrome. Method: A nutritional intervention based on the Mediterranean Diet was performed in 282 patients after Acute Coronary Syndrome, attended at the cardiology ranked hospitals in the state of Sergipe. The intervention was carried out in two appointments, with interval of 90 days between the first and the second, through individualized nutritional care. During the consultations, the food intake frequency questionnaire was applied, anthropometric measures were checked and a dietary prescription was made based on this food pattern. Results: After nutritional intervention, patients significantly increased adherence to Mediterranean dietary patterns (p <0.001). There was no significant difference in adherence to the intervention between patients assisted by the Brazilian Unified Health System and the Supplementary Health Network. The mean of BMI, neck and waist circumferences had a significant reduction (p <0.001) in the interval between the first and the second query.